2009
DOI: 10.1086/605926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Skin Preparation on Postoperative Wound Infection Rates A Prospective Study of 3 Skin Preparation Protocols

Abstract: OBJECTIVE To compare the effects of different skin preparation solutions on surgical-site infection rates. DESIGN Three skin preparations were compared by means of a sequential implementation design. Each agent was adopted as the preferred modality for a 6-month period for all general surgery cases. Period 1 used a povidone-iodine scrub-paint combination (Betadine) with an isopropyl alcohol application between these steps, period 2 used 2% chlorhexidine and 70% isopropyl alcohol (ChloraPrep), and period 3 us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 21 publications
4
163
2
7
Order By: Relevance
“…Climo et al compared the infection rates of intensive care unit patients following daily bathing with either soap and water (2,670 patients) or chlorhexidine solution (2,650 patients) over a one year period [5]. The authors reported a significantly lower incidence of acquisition of methicillin-resistant Staphylo- Swenson et al compared the surgical infection rates following operating room skin preparation with one of three solutions: (1) povidone-iodine scrub and paint, (2) 2% chlorhexidine/70% isopropyl paint and (3) iodine povacrylex paint [19]. The authors found a significantly higher post-operative infection rate with the use of the chlorhexidine preparation (8.2%) as compared to the other regimens (both 4.8%, p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Climo et al compared the infection rates of intensive care unit patients following daily bathing with either soap and water (2,670 patients) or chlorhexidine solution (2,650 patients) over a one year period [5]. The authors reported a significantly lower incidence of acquisition of methicillin-resistant Staphylo- Swenson et al compared the surgical infection rates following operating room skin preparation with one of three solutions: (1) povidone-iodine scrub and paint, (2) 2% chlorhexidine/70% isopropyl paint and (3) iodine povacrylex paint [19]. The authors found a significantly higher post-operative infection rate with the use of the chlorhexidine preparation (8.2%) as compared to the other regimens (both 4.8%, p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…2 We found that rates of SSIs were significantly decreased when iodophore-based skin preparation solutions containing IPA were used, compared with SSI rates when solutions of chlorhexidine plus IPA were used. Because all preparation protocols included IPA, we could isolate the nonalcohol component (chlorhexidine, iodine-providone, and iodine povacrylex were used in our study), and we concluded that iodine-based solutions were most likely superior to chlorhexidine-based solutions in both intention-to-treat and per-protocol models.…”
Section: The Importance Of Isopropyl Alcohol In Skin Preparation Solumentioning
confidence: 83%
“…To the Editor-We thank Maiwald et al 1 and Riccio et al 2 for their interest in our meta-analysis, which reported a decreased number of surgical site infections (SSIs) in patients who underwent preoperative skin antisepsis with chlorhexidine-based formulations, compared with patients treated with iodine-based formulations. 3 The authors raise an interesting point, suggesting that the effectiveness of chlorhexidine-based formulations may be attributable to alcohol rather than to chlorhexidine.…”
Section: Reply To Maiwald Et Al and Riccio Et Almentioning
confidence: 99%
“…Additionally emergence of anti-microbial resistance among the common organisms to conventional antibiotics especially in developing countries due to their irrational practices made the treatment of this seemingly easy condition more difficult. 4,9 The inoculum size, virulence and invasive capability of the organisms have been reported to influence the risk of infection. Moreover, the physiological state of the tissue in the wound and immunological integrity of the host also has equal importance in determining occurrence of infection.…”
Section: Discussionmentioning
confidence: 99%